2001
DOI: 10.1021/es001389t
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of the Cyclic Nitramine Explosive RDX in Natural Soil

Abstract: The sorption-desorption behavior and long-term fate of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) was examined in sterilized and nonsterilized topsoil. Results of this study indicate that although RDX is not extensively sorbed by the topsoil (Ks(d) of 0.83 L/kg), sorption is nearly irreversible. Furthermore, there was no difference in the sorption behavior for sterile and nonsterile topsoil. However, over the longterm, RDX completely disappeared within 5 weeks in nonsterile topsoil, and hexahydro-1-nitroso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 23 publications
4
102
0
Order By: Relevance
“…5). Moreover, a binding site for FadR-like proteins (48), such as XplR, occurs 5 bp from the Ϫ35 promoter region of cyp151C (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Moreover, a binding site for FadR-like proteins (48), such as XplR, occurs 5 bp from the Ϫ35 promoter region of cyp151C (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Of the nitroaromatic and nitramine explosives that exist on these sites, hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) has a low sorption capacity (48) and can migrate through soil into surface water and groundwater (15). RDX-contaminated groundwater also has been found at sites affected by manufacturing, storage, or disposal facilities (19).…”
mentioning
confidence: 99%
“…TNX, the trinitroso metabolite, is less stable and may degrade via several putative pathways in situ (29). However, several reports have demonstrated that TNX may accumulate during RDX biodegradation (41,44,50), which suggests that the ultimate fate of the nitroso metabolites depends on the site conditions. Initial experiments with MNX and DNX suggested reduction in less than 2 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the soil sorption coefficient values for RDX range from 63.1 to 270 indicating a medium to high mobility (Swann et al, 1983). RDX can thus be expected to easily leach into groundwater creating a major environmental problem (Sheremata et al, 2001). The toxicity of RDX has been well documented since many people involved with military activities suffered from generalized convulsions, muscular twitching, hyperactive reflexes, headaches, severe nausea and vomiting, hematuria, and loss of memory within several hours of ingesting 25-180 g C-4 explosive (containing 91% of RDX) (Stone et al, 1969).…”
Section: Introductionmentioning
confidence: 99%